2015
DOI: 10.1038/nn.4115
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood matters: divergent patterns of stress-induced plasticity across the brain

Abstract: The fact that exposure to severe stress leads to the development of psychiatric disorders serves as the basic rationale for animal models of stress disorders. Clinical and neuroimaging studies have shown that three brain areas involved in learning and memory--the hippocampus, amygdala and prefrontal cortex--undergo distinct structural and functional changes in individuals with stress disorders. These findings from patient studies pose several challenges for animal models of stress disorders. For instance, why … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
169
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 216 publications
(184 citation statements)
references
References 151 publications
8
169
0
Order By: Relevance
“…Stress is known to affect the plasticity and excitability of the hippocampus (27). Together with the amygdala and prefrontal cortex, the hippocampus is part of the complex circuitry involved in mammalian trait anxiety, and its substantial role has been acknowledged (5,7,8,28). We show that in the hippocampus, LSD1/neuroLSD1 repression of plasticity genes can be exerted in association with the transcription factor SRF.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Stress is known to affect the plasticity and excitability of the hippocampus (27). Together with the amygdala and prefrontal cortex, the hippocampus is part of the complex circuitry involved in mammalian trait anxiety, and its substantial role has been acknowledged (5,7,8,28). We show that in the hippocampus, LSD1/neuroLSD1 repression of plasticity genes can be exerted in association with the transcription factor SRF.…”
Section: Discussionmentioning
confidence: 86%
“…Seminal studies have shown that mice experiencing different forms of stress, including psychosocial stress, promote stress-related plasticity through epigenetic changes at specific genes, including brain-derived neurotrophic factor (BDNF) and immediate early genes (IEGs) (2)(3)(4). These modifications induce contrasting structural and functional changes in the hippocampus and the amygdala (5), brain areas responsible for the expression of anxiety-like behavior (5)(6)(7)(8). A decrease in neural activity in the hippocampus caused by the loss of dendritic arbors and spines is associated with posttraumatic stress disorder and recurrent depressive illness (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It also plays a central role in the stress response, both promoting downstream hypothalamic-pituitaryadrenal (HPA) axis stimulation and receiving HPA axis feedback (8). Engagement of the stress system can fundamentally change amygdala structure and function, especially as a result of ELS (2,(9)(10)(11). Moreover, the amygdala is likely a component of the neural circuit involved in antidepressant action (12,13), and the antidepressant response is modified by prior stress exposure (10,14).…”
mentioning
confidence: 99%
“…For example, stress paradigms that induce depressive-like behaviors result in hypertrophy of the amygdala, potentially through an increase of dendritic arborizations and spines (1,9). Parallel physiological changes contribute to a sensitization of amygdala engagement (9).…”
mentioning
confidence: 99%